A matlab-based frequency-domain electromagnetic inversion code (FEMIC) with graphical user interface. (February 2017) - Elwaseif, M.; Robinson, J.; Day-Lewis, F.D.; Ntarlagiannis, D.; Slater, L.D.; Lane, J.W.; Minsley, B.J.; Schultz, G.
Abstract: We present a new Matlab-based 1 frequency-domain electromagnetic (EM) inversion code (FEMIC) for analysis of datasets collected using multi-frequency EM-induction instruments. The code includes routines for data filtering and calibration, forward modeling, inverse modeling, image appraisal (i.e., calculation of the depth of investigation), and visualization. A one-dimensional forward model is assumed, but two or three dimensional lateral regularization constraints can be applied during the inversion. The code can take advantage of the parallel-processing capabilities of multi-processor computers, thus facilitating efficient inversion of large datasets. Synthetic and field examples demonstrate the operation of the FEMIC code and showcase its capabilities. Source code is provided as material supplementary to this paper to allow modifications and extensions by others.